Cook Like A Boss: An effective co-created multidisciplinary approach to improving children's cooking competence. (1st January 2022) - Dean, Moira; O'Kane, Chloe; Issartel, Johann; McCloat, Amanda; Mooney, Elaine; McKernan, Claire; Brooks, Stephanie; O'Kane, Niamh; Crowe, William; Murphy, Blain; Lavelle, Fiona
Abstract: Cooking interventions are emphasised as promising methods for changing children's food-related preferences, attitudes and behaviours. However, criticisms remain, including relatively weak intervention designs; lack of validated tools, and limited underpinning theory. Therefore, this research aimed to assess the effectiveness of a theory-driven co-created children's cooking intervention with underpinning rationale for the content, using a validated measure. 'Cook Like A Boss' was a one week, controlled cooking camp style intervention. Thirty two children aged 10–12 years participated. The intervention was developed using the Cook-Ed model for planning, implementing and evaluating cooking programs and was underpinned by Social Learning theory and Experiential Learning theory. The intervention content was developed in a co-creation process with the research team, a chef and the children. The underlying developmental skills required for the recipes were assessed to ensure they were age-appropriate. Children completed pre and post measurements including perceived cooking competence. Process evaluations were also gathered. There was a significant increase in perceived cooking competence after the intervention (P < 0.05) and a significant difference between the intervention and control group (P < 0.001). Additionally, process evaluations found the intervention to have high fidelity and dose received and that it was received extremely positively. The 'Cook Like A Boss' children's cooking camp was an effective multidisciplinary co-created intervention with a vulnerable group, e.g. children, guided by a model and underpinned by theory. The content was developed to ensure it was age-appropriate and achievable for the children. This approach could act as a template for future children's cooking interventions.